Primary School Curriculum Contributing to Plant Blindness: Assessment Through the Biodiversity Perspective - Amprazis, Alexandros; Papadopoulou, Penelope (Advances in Ecological and Environmental Research, 2018)
Biodiversity loss is already an important issue as planet Earth loose species at an alarming rate. This loss has a direct effect on humanity for the capacity of ecosystems to provide welfare, depends on biodiversity. So, no organism can be ignored or be underestimated, as this is happening with plants according to the “Plant Blindness” hypothesis. The limited plant references in subject matter taught in schools are listed among the causes of this phenomenon. Aim of this research is to analyze Greek primary school curriculum according to the grounded theory principles in order to clarify whether they shape attitudes and add to knowledge regarding plant life. According to the results, plant morphology and plant physiology seem to be adequately analyzed throughout the science curriculum. On the contrary, references about the importance of plants for human welfare and life’s evolution on earth are almost lacking. Plant life seems to be examined rather incompletely in the Greek primary school. These findings bring to light issues relating to curricular effectiveness and enhance the general concern about the reduced emphasis on plant life in educational systems worldwide. Hence, a need emerges for revising curriculum and textbooks in order to eliminate deficiencies in plant knowledge.